2016
DOI: 10.1371/journal.pone.0159356
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Kinect Software Tool to Classify Movements during Active Video Gaming

Abstract: While it has been established that using full body motion to play active video games results in increased levels of energy expenditure, there is little information on the classification of human movement during active video game play in relationship to fundamental movement skills. The aim of this study was to validate software utilising Kinect sensor motion capture technology to recognise fundamental movement skills (FMS), during active video game play. Two human assessors rated jumping and side-stepping and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Initially developed as an entertainment device, e.g., used for dancing games, the Kinect sensor is now in widespread research use, including neuro-rehabilitation (31), assessment of post-stroke movement impairment (32), and classification of movements during active video gaming (33). In our study of 30 patients with PD and 33 healthy controls, we found a highly significant association between prolonged time of motor performance in the Motorgame and higher scores of MDS-UPDRS items related to right hand movements (bradykinesia).…”
Section: Discussionmentioning
confidence: 99%
“…Initially developed as an entertainment device, e.g., used for dancing games, the Kinect sensor is now in widespread research use, including neuro-rehabilitation (31), assessment of post-stroke movement impairment (32), and classification of movements during active video gaming (33). In our study of 30 patients with PD and 33 healthy controls, we found a highly significant association between prolonged time of motor performance in the Motorgame and higher scores of MDS-UPDRS items related to right hand movements (bradykinesia).…”
Section: Discussionmentioning
confidence: 99%
“…Computer vision uses an array of techniques from fields such as engineering and machine learning to extract meaningful information (e.g., facial features and hand gestures) from digital images including video [7]. While a small number of studies have used custom computer vision algorithms to convert video-recorded PA behaviors into quantifiable PA signals [6,[8][9][10][11], no study has validated such a method for estimating PA volumes and intensities in young children from these signals. A recent report pointed toward the potential benefits 2 of 18 of using computer vision, rather than wearable sensors, to measure children's physical activity while indoors at school [12].…”
Section: Introductionmentioning
confidence: 99%
“…Of the available studies that have used computer vision to specifically estimate PA volumes [6,8,[10][11][12], few have expressly calibrated an algorithm to quantify and classify activity data in children [8]. A study of 10-year-old children appears to be the first to demonstrate the feasibility of using a ceiling-mounted camera to automatically derive estimates of PA velocities in bidimensional space [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to bypass the lower extremities inaccuracy a technique that relies on knee joint relative angle has been proposed to detect foot-off and foot contact during the gait cycle [9]. The Kinect was successfully used for the classification of human movement during active video game play in relationship to fundamental movement skill [10].…”
Section: Introductionmentioning
confidence: 99%